CDK4/6 and PDGFRA Signaling as Therapeutic Targets in Diffuse Intrinsic Pontine Glioma - Hoeman, Christine; Shen, Chen; Becher, Oren J. (Frontiers in Oncology, 2018)
Diffuse Intrinsic Pontine Gliomas are incurable childhood brain tumors whereby the standard of care is focal radiation, a treatment that provides temporary relief for most patients. Surprisingly, decades of clinical trials have failed to identify additional therapies that can prolong survival in this disease. In this conference manuscript, we discuss how genetic engineered mouse modeling techniques with the use of a retroviral gene delivery system can help dissect the complex pathophysiology of this disease. With this approach, autochthonous murine DIPG models can be readily induced to 1) help interrogate the function of novel genetic alterations in tumorigenesis, 2) identify candidate cells-of-origin for this disease, 3) address how region-specific differences in the central nervous system influence the process of gliomagenesis, and 4) evaluate novel therapeutics in an immunocompetent model.